2022
DOI: 10.1007/s00246-022-02977-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Assessment in Children with MIS-C: Late Magnetic Resonance Imaging Features

Abstract: Multisystem Inflammatory Syndrome (MIS-C) is a new entity that emerges 2-4 weeks after the SARS-CoV-2 infection in children. MIS-C can affect all systems, the most severe of which is cardiac involvement. The duration of the cardiac symptoms is still uncertain and may be persistent or prolonged. The American College of Rheumatology Clinical Guidelines recommends cardiac magnetic resonance imaging (MRI) 2-6 months after the diagnosis of MIS-C in patients presenting with significant transient left ventricular (LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
1
7
2
Order By: Relevance
“…It has been reported that patients with hypotension, shock, and myocarditis are admitted to the ICU more frequently than patients with coronary dilatation/aneurysm (7,10,11,22,23). Laboratory tests show that pro-BNP and troponin levels are higher during ICU admission (10)(11)(22)(23). In our study, no difference was found between the patients with and without cardiac involvement in relation to ICU admission.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…It has been reported that patients with hypotension, shock, and myocarditis are admitted to the ICU more frequently than patients with coronary dilatation/aneurysm (7,10,11,22,23). Laboratory tests show that pro-BNP and troponin levels are higher during ICU admission (10)(11)(22)(23). In our study, no difference was found between the patients with and without cardiac involvement in relation to ICU admission.…”
Section: Discussioncontrasting
confidence: 47%
“…The American College of Rheumatology recommended that all patients be evaluated by echocardiography and cardiac MRI no earlier than 2-6 months after diagnosis to determine the long-term cardiac effects of MIS-C cases (24) (22). Similarly, in our study, cardiac MRI was performed in only 4 of 31 patients 6 months after discharge, and no cardiac pathology was detected in 4 patients.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Thirty‐six healthy pregnant women who had COVID‐19 infection with mild to moderate symptoms according to The National Institutes of Health (NIH) classification in the second trimester of pregnancy were included in the patient group (COVID group) 10,11 . Infection was confirmed with a reverse transcription‐polymerase chain reaction (RT‐PCR) test with a nasopharyngeal swab in all patients and none of them were hospitalized.…”
Section: Methodsmentioning
confidence: 99%
“…There were 206 publications that resulted with our keyword search on MIS-C and follow-up between 2020 and 2022. Eleven published studies fit the inclusion criteria with a total of 343 participants (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). All studies included patients who met criteria for MIS-C per the CDC guidelines (see Figure 1).…”
Section: Yield Of the Searchmentioning
confidence: 99%